Beach cleaning machine / Muhammad Ashraf Aiman Hairulnizam, Noor Hafiz Noordin and Mohd Ghazali Mohd Hamami - Hairulnizam, Muhammad Ashraf Aiman; Noordin, Noor Hafiz; Mohd Hamami, Mohd Ghazali (School of Mechanical Engineering, 2023)
Beach pollution has emerged as a critical issue, yet many people remain unaware of its severity. The problem continues to worsen over the years, adversely affecting humans, wildlife, and the environment. While various types of beach cleaning machines have been developed, they are often large and complex to operate. There is a market need for a compact, user-friendly, and portable beach cleaning machine. The objective of this study is to analyze the issue of beach pollution and design a mini beach cleaning machine that can be remotely controlled by users. The fabrication process involves cutting, bending, drilling, and grinding. The machine is primarily made of aluminium due to its affordability, lightweight nature, durability, and corrosion resistance. This project offers significant benefits by improving the quality of life for living beings, safeguarding the environment, and benefiting communities, particularly those residing near beaches. In conclusion, this beach cleaning machine is highly efficient, free of operational issues, and fulfills its purpose of effectively removing pollution from beaches